Perfil inflamatório gengival de pacientes internados em Unidade de Terapia Intensiva com a COVID-19 - Estudo Piloto - Silva, Gustavo Henrique Gomes da (2021)
Although not fully understood, there are studies on the impact of periodontal disease on COVID-19, as it could increase the severity of cases positive for the virus, causing bacterial superinfection, host hyperresponsiveness, and overstimulation of the immune system. The objective of this study was to evaluate the gingival inflammatory profile of patients with COVID-19 admitted to the COVID ward of the Western Paraná State University Hospital (HUOP) in Cascavel, Paraná, through clinical research with quantitative analysis. The collection of patient data, such as age, gender, exams, and health history, was performed by searching the hospital information system - Tasy®. After being evaluated according to the inclusion criteria, the patients were divided into two groups: patients with respiratory failure without a diagnosis of COVID-19 (control group) and patients with respiratory failure diagnosed with COVID-19 (case group). Hematological data were collected, and a clinical examination was performed to evaluate the plaque index, probing depth, clinical level of insertion and bleeding on probing, and gingival crevicular fluid was collected to analyze the amount of fluid. A reduction in the periodontal inflammatory profile of COVID-19 patients was observed; however, dexamethasone therapy in this group may have led to suppression of periodontal inflammation.